From 2000 to 2022 evaluate of land ecological security and reveal obstacle factors in Heilongjiang Province - Wang, Yujia; Gan, Jing; Guo, Fuyou; Dong, Erwei; Liu, Jiafu; Zhao, Wenqi (Frontiers in Earth Science, 2025)
At present, the global environmental problems are intensifying, and land resources are facing multiple dilemmas such as degradation, pollution and shortage. The rise of the concept of sustainable development, the enhancement of public ecological awareness and the promotion of relevant policies and regulations have jointly promoted the generation and development of land ecological security research. This study evaluated the land ecological security of Heilongjiang Province from 2000 to 2022, found out the main factors affecting the land ecological security, provided the basis for scientific formulation of corresponding measures, provided the guarantee for the sustainable development of regional social economy and agriculture, and maintained the long-term coordinated development of the land natural, social and economic complex. Based on the PSR model, this study constructs an index system for evaluating land ecological security. It employs a comprehensive index model to assess and utilizes the entropy-weighted TOPSIS method to determine the weights of various indicators. It calculated the comprehensive index of Heilongjiang Province from 2000 to 2022. Drawing upon relevant literature, this research establishes the land ecological security level of the region. The obstacle factor diagnosis model is used to analyze the main obstacle factors at each level, and corresponding countermeasures are proposed based on the results. The main results are as follows: (1) From 2000 to 2022, the level of land ecological security in Heilongjiang Province has generally shown a fluctuating upward trend, with the safety level changing from dangerous to relatively safe and moving towards a favorable direction. However, it remained mostly in an unsafe state for the past 20 years; (2) The main threats at the criterion layer have changed significantly, with obstacle degrees rising to 59% for pressure systems and 36% for status systems while decreasing to 5% for response systems. Currently, the main threat comes from pressure systems; (3) The main obstacle factors at the indicator layer have evolved from the proportion of tertiary industry output value and effective irrigation area of arable land to pure amount of chemical fertilizer applied in agriculture and proportion of forest area. In 2022, major factors affecting land ecological security in Heilongjiang Province are pure amount of chemical fertilizer applied in agriculture, proportion of forest area, industrial solid waste generation volume, pesticide use volume, and per capita water resources. This study evaluated the land ecological security in Heilongjiang Province, revealed its influencing factors, and put forward specific suggestions for local construction.